Regulatory Barriers to Consumer Protection in Digital Marketplaces - Ariawan, Ariawan (Journal of Human Rights, Culture and Legal System, 2025)
The rapid expansion of digital technology has transformed commercial activities from conventional face-to-face interactions into online marketplaces, creating new patterns of consumer vulnerability. Although Indonesia has implemented various regulations through the Consumer Protection Law, the Electronic Information and Transactions Law, and government regulations, existing norms remain unable to address legal risks that arise within digital transactions. This study examines three core issues: first, legal problems and challenges in the implementation of consumer protection for online transactions in Indonesia; second, regulatory differences between Indonesia and Malaysia in governing online buying and selling activities; and third, an ideal policy model for strengthening consumer protection in the digital economy. This research adopts a normative juridical method supported by statutory, conceptual, and comparative approaches. Legal materials are analyzed qualitatively to assess normative gaps and identify reform needs. The study finds three principal results. First, Indonesian regulations remain fragmented, outdated, and unable to accommodate digital-era risks such as information asymmetry, data misuse, and platform liability. Second, Malaysia provides a more comprehensive regulatory framework, particularly regarding transaction validity, business liability, dispute resolution, and sanctions. Third, effective consumer protection requires an integrated reform model that strengthens legal substance, institutional structure, and legal culture to build a more secure, transparent, and equitable digital transaction ecosystem.